Relating pessimistic memory predictions to Alzheimer's disease brain structure. (December 2016) - Genon, Sarah; Simon, Jessica; Bahri, Mohamed Ali; Collette, Fabienne; Souchay, Céline; Jaspar, Mathieu; Bastin, Christine; Salmon, Eric
Abstract: Patients with Alzheimer's disease (AD) show impairment of episodic memory and related metacognitive processes. The present study examined subjective metacognitive judgments preceding objective memory retrieval and investigated the neural correlates of pessimistic predictions for successfully retrieved memories in AD patients. AD patients and healthy older (HO) participants provided predictive judgments on their recognition performance before retrieval of famous (semantic) and recently learned (episodic) names. Correlations between gray matter volume (GMV) in T1 images and behavioral scores were examined with multivariate (partial least square – PLS) and univariate (general linear model – GLM) analyses in AD patients. AD patients showed a significant proportion of successful name recognition preceded by pessimistic prediction in episodic memory. PLS revealed that the behavioral pattern in AD patients was related with a mainly right lateralized pattern of GMV decrease including medial temporal lobe and posterior cingulate cortex (PCC), but also right ventrolateral prefrontal cortex (VLPFC). GLM further confirmed that pessimistic prediction negatively correlated with GMV in VLPFC. Thus, impaired monitoring processes (possibly influenced by inaccurate beliefs) allowing inferences about one's own memory performance are primarily related to decrease GMV in VLPFC in AD patients.